2018
DOI: 10.4244/eij-d-17-00461
|View full text |Cite
|
Sign up to set email alerts
|

Functional comparison between the BuMA Supreme biodegradable polymer sirolimus-eluting stent and a durable polymer zotarolimus-eluting coronary stent using quantitative flow ratio: PIONEER QFR substudy

Abstract: Quantitative flow assessment nine months after stenting did not differ between B-SES and R-ZES, despite a significant difference in in-stent late lumen loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Although serial 2D‐QCA (e.g., LLL) has been used and benchmarked as a surrogate to assess the efficacy of coronary devices, 1 a recent meta‐analysis indicated that LLL may no longer reflect device efficacy in the current DES era 18 . In this meta‐analysis, the best cut‐off value of LLL for predicting TLR was 0.50 mm; below this threshold, LLL may not always correlate in a linear manner with TLR, 18 and a higher LLL may be associated with lower clinical TLR rates as demonstrated with the BuMA stent compared to the resolute DES 12 . QFR may be considered the new standard in evaluating coronary device performance over time.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Although serial 2D‐QCA (e.g., LLL) has been used and benchmarked as a surrogate to assess the efficacy of coronary devices, 1 a recent meta‐analysis indicated that LLL may no longer reflect device efficacy in the current DES era 18 . In this meta‐analysis, the best cut‐off value of LLL for predicting TLR was 0.50 mm; below this threshold, LLL may not always correlate in a linear manner with TLR, 18 and a higher LLL may be associated with lower clinical TLR rates as demonstrated with the BuMA stent compared to the resolute DES 12 . QFR may be considered the new standard in evaluating coronary device performance over time.…”
Section: Discussionmentioning
confidence: 81%
“…Our results are similar to prior retrospective series. In a sub‐study of the SYNTAX II trial, 341 out of 1,177 lesions (29%) were not analyzable by QFR, 11 and the retrospective PIONEER QFR sub‐study showed that QFR was not feasible in 13% of lesions 12 . When QFR is planned in a prospective manner, previous reports indicated that it is feasible in almost all cases 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a surrogate marker of stent efficacy, the potential applicability of the angiography-derived FFR as a new-generation QCA was reported [79]. A patient-level meta-analysis reported that even a statistically significant difference in angiographic late lumen loss within the low value range did not have a clinical impact [80].…”
Section: Angiography-derived Ffrmentioning
confidence: 99%